ANALYZING THE CULTURAL WORDS TRANSLATION OF "NOT ONLY NASI GORENG" BY SURYATINI N. GANIE(A CASE STUDY OF INDONESIAN-ENGLISH TRANSLATION) - Zia Kemala, - (2010)
This research paper is entitled 'Analyzing the Cultural Words Translation in "Not Only Nasi Goreng" by Suryatini N. Ganie'. The aims of the study are to investigate the types of cultural words commonly found in the recipe book and to figure out the translation procedures used by the translator in translating the cultural words into English and whether the translation is accurate or not. The study employed a qualitative research design embracing characteristics of a case study in a form of text analysis approach. This method allows the writer to make a systematic and factual description of the obtained data. The data were all the cultural words found in the recipe book. The data were categorized based on categories of cultural words as suggested by Newmark (1988:95) and other experts, including Robinson (1985:18), Tomalin and Stempleski (1996). The cultural word categories are ecology, material, social, organization, and habits. The findings of the study show that material culture was the most frequent category of cultural words found in the recipe book. The translation procedures are in line with those proposed by Newmark (1988:81) and other experts, including Graedler (2000:3), Harvey (2000:2-6), Vinay and Darlbenet (2000:84), Jackobson (as cited in Leonardi, 2000), and Sarcevic (as cited in Ordudari, 2008). The translation procedures are literal, transference, naturalization, cultural equivalent, functional equivalent, descriptive equivalent, through translation, transpositions, compensation, couplets, and notes. The findings of the study show that descriptive equivalent was the most frequent procedure used in translating the cultural words found in the recipe book. Most of the translations are appropriate and make sense in the target language since they fulfill the criteria of a good translation, such as give a complete transcript of the original text's ideas and attitudes, preserve the original text's character of the style and manner, have all the ease of the original composition (Tytler, 1907). The translation also covers the factors of translation judgment namely accuracy, clarity, and naturalness (Larson, 1984), and fulfill the equivalence (Nida, 1971) and skopos theory (Vermeer, 1989). Those criteria can be used as a reference and guide lines for translators to produce a qualified translation.